SMART CAMP: Environmental Sustainability Through Intelligent Automation Technologies - Kohn, M.; Chang, Elizabeth; Karduck, A.; Talevski, Alex (IEEE Computer Society, 2010)
A "Smart Camp" solution is a new approach to provide a mining community consisting of multiple households in a remote area in Western Australia with a intelligent wireless network and automated information system. This system intends to automate, control and monitor numerous household devices; supplies the tenants with multi-media services and aims to reduce energy consumption as well as improving the workers habitat. This paper theorizes the big picture with considerations on: how to set up, integrate and create a cost-effective "smart" wireless home automation network solution. It attempts to improve employee quality of life while simultaneously reducing energy consumption and the related emissions. Therefore, the latest Wireless Technologies in the field of domotics will be discussed and the importance of environmental sustainability and energy awareness will be outlined.